The Moderating Role of CEO's Education on the effect of Corporate Governance Mechanism and Firm's Performance in Saudi Arabia's Non- Financial Sector - lubna, javed (UNIMAS, 2022)
Recent scandals at Wells Fargo and Equifax-the financial crisis of 2008 and the new millennium scandals in Enron, WorldCom, Tyco, and Qwest have put back on the policy agenda and intensified debate on the efficacy of corporate governance mechanisms as means of increasing firm performance. At the backdrop of this scenario, Saudi Arabia has lately revamped its codes for corporate governance. Empirical work in corporate governance has undergone a remarkable growth, however despite the volume of empirical evidence, there has been no consensus as to which corporate governance mechanism resolves the agent principal conflict and increase performance. Therefore, this study has addressed this problem by creating and validating corporate governance mechanisms model on 114 non-financial firms listed on the Saudi stock Exchange Tadawul spanning the period of 2015–2018.